The Effect of Grammage on Bulk in A-Grade Printing Paper Based on Taro Skin and Oil Palm Fronds - Putri Nadila; Ety Jumiati; Miftahul Husnah (Universitas Negeri Medan, 2026)
The use of wood as the main raw material for paper production causes environmental problems such as deforestation. This study aims to analyze the physical characteristics of paper made from taro skin and oil palm fronds through the parameters of grammage and bulk. Grammage and bulk are important parameters in determining the quality of printing paper A according to SNI 7274:2008. The composition variations used were samples A (60%:40%), B (40%:60%), and C (20%:80%). The results show that the lowest grammage value is 79 g/m2 in the 20%:80% variation and the highest grammage value is 90 g/m2 in the 60%:40% variation. For bulk testing, the lowest value was 1.11 cm3/g in the 20%:80% variation and the highest bulk value was 1.46 cm3/g in the 60%:40% variation. All samples met the SNI 7274:2008 standard for A-grade printing paper, with a grammage limit of 50-100 g/m2 and a maximum bulk of 1.5 cm3/g. Increasing the proportion of oil palm fronds reduced the grammage but increased the bulk. This study proves the potential of taro skin and oil palm fronds as raw materials for environmentally friendly paper.